Synthesis of Cathode Material Li2FeTiO4 for Lithium-Ion Batteries by Sol–Gel Method - Pengqing Hou; Qi Sun; Shengxue Yan; Guanglong Li; Yingdong Qu; Shaohua Luo (Batteries)
The development of a simple and reliable strategy to synthesize cathode materials is crucial for achieving the overall high performance of rechargeable lithium batteries, which has proved to be quite challenging. Herein, we report a simple sol–gel method for the synthesis of Li2FeTiO4 cathode materials. The reaction mechanism of Li2FeTiO4 crystals can be divided into five stages: including the breakage of the coordination bond; the thermal decomposition of citric acid; the thermal decomposition of metal salts and the reduction of trivalent iron and the formation of Li2FeTiO4 crystals. Finally, the optimum calcination temperature for the preparation of Li2FeTiO4 cathode materials was explored. The Li2FeTiO4 cathode material prepared at 700 °C provides a discharge-specific capacity of 121.3 mAh/g in the first cycle and capacity retention of 89.2%. Our results provide new insights into the application of Li2FeTiO4 cathode materials.